An Analysis on Students’ Difficulties in Mastering Vocabulary - Marselina, Pika; Ayu, Citra; Hardi, Vitri Angraini (Journal of English Language and Education, 2024)
This study focuses on students' difficulties in mastering English vocabulary. The purpose of this study was to determine the students' difficulties in mastering vocabulary. This study uses a qualitative research design with a descriptive approach. To obtain data, the researcher used a questionnaire. This research was conducted by giving questionnaires to the participants. The findings revealed that shows that 25% strongly agree. This shows that students still have difficulty in using vocabulary that has many meanings correctly; 25% agree; 25% disagree; 12% disagree and 14% students vote. It can be concluded Class X students of SMAN 1 Bangkinang still have many difficulties in mastering vocabulary.